Tingkat Penggunaan Tepung Daun Indigofera (Indigofera zollingeriana) Yang Berbeda Terhadap Performans Itik Alabio (Anas Platyrhynchos, Borneo) Jantan: Different levels of use of Indigofera (Indigofera zollingeriana) leaf flour on the performance of male Alabio ducks (Anas platyrhynchos, Borneo) - Sulaiman, Abrani (www.ulm.ac.id, 2025)
This study aimed to evaluate the effects of different inclusion levels of Indigofera zollingeriana leaf meal on the production performance and economic efficiency of male Alabio ducks. The research was motivated by the need for high-quality, cost-effective local feed ingredients to reduce reliance on conventional feedstuffs. A completely randomized design was employed with five treatments (0%, 5%, 10%, 15%, 20% Indigofera leaf meal) and five replications, each with four ducks. Diets were formulated to be iso-protein (16%) and iso-caloric (±2,900 kcal/kg) and were provided ad libitum for five weeks. Results indicated that inclusion of Indigofera leaf meal up to 20% did not significantly affect feed intake, body weight gain, or feed conversion ratio. The highest final body weight was achieved at 15% inclusion (1,322 g/bird), while the highest Income Over Feed Cost was recorded at 20% inclusion (Rp 14,531.15/bird). These findings highlight a balance between biological performance and economic efficiency, where 15% is optimal for growth, while 20% is more profitable financially. This research contributes to the sustainable utilization of local alternative feed resources and provides a scientific basis for economical and efficient poultry diet formulation. Keywords: Alabio duck, Indigofera zollingeriana, production performance, ration conversion, economic efficiency